Colossal tunability in high frequency magnetoelectric voltage tunable inductors. Issue 1 (December 2018) - Yan, Yongke; Geng, Liwei; Tan, Yaohua; Ma, Jianhua; Zhang, Lujie; Sanghadasa, Mohan; Ngo, Khai; Ghosh, Avik; Wang, Yu; Priya, Shashank
Abstract The electrical modulation of magnetization through the magnetoelectric effect provides a great opportunity for developing a new generation of tunable electrical components. Magnetoelectric voltage tunable inductors (VTIs) are designed to maximize the electric field control of permeability. In order to meet the need for power electronics, VTIs operating at high frequency with large tunability and low loss are required. Here we demonstrate magnetoelectric VTIs that exhibit remarkable high inductance tunability of over 750% up to 10 MHz, completely covering the frequency range of state-of-the-art power electronics. This breakthrough is achieved based on a concept of magnetocrystalline anisotropy (MCA) cancellation, predicted in a solid solution of nickel ferrite and cobalt ferrite through first-principles calculations. Phase field model simulations are employed to observe the domain-level strain-mediated coupling between magnetization and polarization. The model reveals small MCA facilitates the magnetic domain rotation, resulting in larger permeability sensitivity and inductance tunability. Voltage tunable inductors (VTIs) with high working frequency and tunability are desired for new design of energy efficient electronics. Here the authors demonstrate magnetoelectric VTIs operating up to 10 MHz with tunability over 750% via strain mediated magnetoelectric effect and magnetocrystalline anisotropy cancellation strategy.